Pelatihan Penggunaan Aplikasi Wordwall Sebagai Media Pembelajaran Interaktif Untuk Guru Sekolah Dasar di Kota Depok: Pengabdian - Rhetno Wardhani, Dyah; Erlangga, Fajar; Abdillah, Rahman; Ramdhan, Vickry; Kuncoro, Adhityo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This program aimed to enhance the competencies of elementary school teachers in Depok City in developing interactive digital learning media using the Wordwall application. The activities were carried out in the form of training and direct mentoring, focusing on the creation and implementation of game-based learning media. The implementation methods included demonstration, hands-on practice, and guided assistance. The results of the program indicate that participants were enthusiastic and successfully created simple learning media using Wordwall. Based on observations throughout the activities, the teachers demonstrated improved skills and increased interest in integrating digital technology into the teaching and learning process. This program is expected to serve as an initial step in supporting digital learning transformation in elementary schools.